Syair “Ghayati” Karya Ibrahim Tuqan (Kajian Ilmu ‘Arudh) - Muhammad Irfan Shiddiq; Sayyed Zuhdi (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
This research is entitled "Syair Ghayati Karya Karya Ibrahim Tuqan (Study of 'Arudh Science)" which aims to analyze the ghayati poetry by the Palestinian poet Ibrahim Tuqan using the science of 'arudh. The main focus of this research is to identify the patterns or bahr syi'riyyah used in the poetry and examine the various changes that appear in it. This research uses a qualitative descriptive method because the object of study is a literary text that is analyzed in depth, then the results are presented in the form of a narrative description. The data sources for this research were obtained through literature studies by reviewing books, journals, and other relevant documents. Based on the results of the analysis, Ibrahim Tuqan's ghayati poetry uses the raml majzu' pattern as the basic structure of the poetry. In addition, changes were also found in the form of zihaf khabn and zihaf 'illah which occurred in several parts of the verse, although there was no 'illah found in the entire poetry. Thus, this research shows how the application of the science of 'arudh can reveal the beauty and dynamics in classical Arabic literary works.